Bioacumulação e parâmetros de estresse oxidativo em Tambaqui (Colossoma macropomum) exposto a MnCl2 em diferentes níveis de oxigênio dissolvido - Gabriel, Diogo (2013)
The aquatic organisms are susceptible to frequent interferences in their habitat, such as oxygen fluctuations and metal contamination. Industrial production and oil exploration, among other activities, release manganese (Mn2+) into the water of the Amazon basin. Manganese may induce oxidative stress (OS) in fish, so a control of the metal in the water as well as in the aquatic organisms is necessary. In this way, the present work aimed at exposing tambaqui (Colossoma macropomum) to Mn2+ for 96 h to assess the LC50-96h in the species and subsequently outline the redox profile of the fish subjected to a sublethal concentration of the metal in normoxia and hypoxia. In the first series of experiments the fish were exposed to normoxia (6 mg/L), hypoxia (0.25 mg/L) and hyperoxia (10 mg/L). Mortality was only observed in hypoxia, with a Mn2+ LC50-96h of 4.03 mg/L. Bioaccumulation occurred in the following order: gills>liver>muscle. During the second series of experiments the fish were subjected to 3.88 mg/L Mn2+ for 96 h in normoxia (6 mg/L). After exposure the fish were euthanized by sectioning the spinal cord and the target tissues, brain, gills, liver and kidney, were excised. Biomarkers of OS were analysed: thiobarbituric acid reactive substances (TBARS), superoxide dismutase (SOD), catalase (CAT), glutathione-S-transferase (GST) and the content of non-protein thiol groups (GSH). In gills there was a significant increase in TBARS levels and in SOD activity, and a reduction in GSH. Decreased levels of TBARS, increased SOD and GST activities, as well as increased GSH, were observed in the hepatic tissue. In brain SOD and CAT activities reduced significantly. An increase in TBARS levels and a decrease in SOD activity were found in the kidney. The induction of OS was clearly observed in this second series of trials, with a different pattern of Mn2+ toxicity in each of the evaluated organs. Bioaccumulation was as follows: gills>kidney>brain>liver. In the third series of experiments tambaqui was subjected to 3.88 mg/L Mn2+ for 96 h under hypoxia (0.25 mg/L). The procedures after exposure, the dissected tissues and the analysed biomarkers of OS were similar to the ones described for the second series, only GSH was not measured this time. In gills and liver there was a rise in the levels of TBARS and a decrease in the activities of SOD and GST. Exposure to Mn2+ did not trigger changes in the levels of TBARS in brain and kidney, but induced a significant increase in SOD activity. A reduction in the levels of GST was also observed in tambaqui kidney. The sequence of bioaccumulation was: kidney>gills>liver>brain. As it was observed in the second series, exposure to Mn2+ caused OS in certain organs, though with a different redox profile in each tissue. Therefore, the experiments allowed attaining Mn2+ LC50-96h in tambaqui. The bioaccumulation values for each organ were not correlated with the findings on OS biomarkers. Furthermore, SOD displayed a key role in the tests. The redox profile obtained in normoxia as well as in hypoxia may lead to further studies which will possibly indicate the tambaqui as a sentinel fish for Mn2+ in the water.